The Impact of Questionnaire Design on Prevalence and Incidence Rates of Self-Reported Delinquency: Results of an Experiment Modifying the ISRD-2 Questionnaire. (February 2013) - Enzmann, Dirk
Based on two samples of juveniles (total n = 1, 629), this experimental study explores effects of modifying the design (not the wording) of a self-report questionnaire on prevalences and incidences of delinquency - the core instrument of the second International Self-Report Delinquency (ISRD-2) study. Research questions are: Do rates of self-reported delinquency differ by questionnaire design? Are there differences in item nonresponse? Do these effects differ by person characteristics, especially self-control? Do effect sizes of predictors of offending differ by questionnaire design? Omitting follow-up questions and reversing the response categories no/yes generates higher levels of self-reported delinquency as to minor offenses. Item nonresponse is affected by the design of filter questions and by person characteristics (e.g., low self-control) correlating with delinquency. Although the modifications reduce underreporting, effects of predictors on delinquency do not differ substantially. Nevertheless, more variance is explained using the modified version data.